2020
DOI: 10.3390/nu12092794
|View full text |Cite
|
Sign up to set email alerts
|

Daily Protein and Energy Intake Are Not Associated with Muscle Mass and Physical Function in Healthy Older Individuals—A Cross-Sectional Study

Abstract: Dietary protein has a pivotal role in muscle mass maintenance with advancing age. However, an optimal dose and distribution of protein intake across the day as well as the interaction with energy intake for the maintenance of muscle mass and physical function in healthy older adults remain to be fully elucidated. The purpose of this study was to examine the association between muscle mass, strength, and physical function, and the total amount and distribution of protein and energy intake across the day in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 64 publications
2
17
0
Order By: Relevance
“…More specifically, those above the median of ABPI as percentage of energy intake showed greater lower-body strength and endurance and greater handgrip strength than those below. Although greater protein intake is thought to be protective from developing sarcopenia [ 34 , 35 , 36 ], a recent cross-sectional study of older Danish adults utilizing methods similar to ours (e.g., three-day food diary and physical activity assessment) reported that protein intake was not related to knee extensor strength, handgrip strength, and 30-s chair stand test performance [ 16 ]. In contrast to their methodology where participants were divided into groups based on relative protein intake, we split ours according to ABPI as a percentage of energy intake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, those above the median of ABPI as percentage of energy intake showed greater lower-body strength and endurance and greater handgrip strength than those below. Although greater protein intake is thought to be protective from developing sarcopenia [ 34 , 35 , 36 ], a recent cross-sectional study of older Danish adults utilizing methods similar to ours (e.g., three-day food diary and physical activity assessment) reported that protein intake was not related to knee extensor strength, handgrip strength, and 30-s chair stand test performance [ 16 ]. In contrast to their methodology where participants were divided into groups based on relative protein intake, we split ours according to ABPI as a percentage of energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…There is a high degree of collinearity between relative intakes of macronutrients and relative energy intake. In fact, one of the main findings from Højfeldt and colleagues’ study of older Danish adults was that relative protein intakes and relative energy intakes are related [ 16 ]. Collinearity can bias estimates of betas in multivariate analyses [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, Coelho-Junior et al [6] indicated that adequate protein consumption is an important intervention to manage frailty, emphasizing the importance of setting the optimal distribution of protein across meals and assessing several protein-related parameters (instead of the only amount of protein intake). In fact, neither the total protein intake nor meal distribution appeared to be associated with muscle mass, strength or physical function in a cohort of Danish older adults [7].…”
mentioning
confidence: 82%
“…Other studies have shown no associations between protein distribution and physical function or strength [9,10]. However, meal-speci c protein dose may have biased ndings in studies assessing protein distribution.…”
Section: Introductionmentioning
confidence: 99%